Technoscience in Progress. Managing the Uncertainty of Nanotechnology - Arnaldi, Simone (IOS Press, 2013)
Nanotechnology seems to escape boundaries and definitions. The “Rush to Nanoscale” spreads throughout different sites and arenas, involving a multiplicity of actors, meanings, and spaces in which they emerge. The ‘uncertainty of nanotechnology’ appears to be both a condition and a consequence of this situation. This volume adds to the collective effort of charting the multiple and heterogeneous dimensions that characterise nanotechnology, by analysing the numerous modalities through which different stakeholders and actors provide definitions, attribute meaning and sense to nano-enabled innovations. The chapters of the book attempt to highlight how nanotechnologies, their discourse, and their actual and potential implications cannot be isolated in laboratories, factories, markets, and separate discussion arenas. Also, the volume examines how it is apparently not possible to bind and/or confine the definition of nanotechnology by referring exclusively to present-day research and applications, as well as to geographical, cultural, and even disciplinary boundaries. Considered together, this collection of essays suggests that the ‘societal experiment’ of nanotechnology has to be explored with a vocabulary that is not just scientific and technical, in order to cross the frontiers between multiple domains, actors, identities, translations, and negotiation processes that occur in the nanotechnology field.